An Intergenerational Exploration of Discipline, Attachment, and Black Mother–Daughter Relationships Across the Lifespan - Seanna Leath; Lamont Bryant; Khrystal Johnson; Jessica Bernice Pitts; Titilope Omole; Sheretta T. Butler-Barnes (Behavioral Sciences)
Discipline is a significant predictor of parent–child attachment and relationship quality across the lifespan. Yet, much of the research on Black families’ disciplinary strategies uses a deficit and myopic lens that focuses on punitive punishment styles (e.g., spanking or taking away privileges). In the current exploratory qualitative study, we used an intergenerational narrative lens and thematic analysis to explore semi-structured interview data from 31 Black mothers (25–60 years, Mage = 46) in the United States around their mothers’ disciplinary practices during their childhood. We explored the connections that Black adult daughters made between their childhood disciplinary practices and their current disciplinary practices with their children, as well as their current relationships with their mothers. Adult daughters varied widely in their retrospective accounts of their mothers’ disciplinary strategies, which we categorized into three themes: (a) punitive, (b) logical, and (c) natural. We also identified three themes around how their mothers’ practices informed their current disciplinary practices with their own children: namely, (d) continuity, (e) mix, and (f) shift. Finally, we identified three themes around the current nature of their mother–daughter relationships: (g) strained, (h) progressing, and (i) healthy. The results highlighted the personal and cultural factors that informed Black women’s disciplinary strategies across two generations of mothers and revealed that when adult daughters shifted away from what they experienced during childhood—it was often towards less punitive strategies. Our exploratory findings also pointed to patterns regarding the extent to which Black adult daughters felt connected, validated, and supported by their mothers. The findings lend insight into Black mother–daughter relationship dynamics, particularly around the importance of communication patterns and emotional connection in the culture of discipline within families.